DAMPAK PEMBANGUNAN JALAN TOL TRANS SUMATERA TERHADAP ALIH FUNGSI LAHAN PERMUKIMAN DAN PERSAWAHAN MASYARAKAT DITINJAU DALAM PERSPEKTIF EKONOMI ISLAM - Fatih Fuadi; M. Ramdani Nasrudin (JURNAL ILMIAH EDUNOMIKA, 2022)
The construction of the toll road which is located in Jatimulyo Village, Jati Agung District, has an impact, one of which is the transfer of community land functions, resulting in changes because it is still in a transitional period. The formulation of the problem in this study is what is the impact of the construction of the Trans Sumatra toll road on the conversion of residential land and community rice fields from an Islamic economic perspective? How is the condition of the community after the conversion of residential land and community rice fields in terms of an Islamic economic perspective? The purpose of this study was to determine how much impact the construction of the Trans Sumatra toll road had on the conversion of community land and rice fields and to determine the condition of the community structure after the conversion of community land functions from an Islamic economic perspective. This type of research is a field research with data collection methods by observation, interviews, questionnaires and documentation. This study uses a qualitative descriptive analysis method. The results of this study show that the construction of the Trans Sumatra Toll Road reduces congestion and with the construction of the existing toll road in Jatimulyo Village, an area of ±495,355.66 is converted for development so as to open a new residential area. In the Islamic concept of toll road construction, including development carried out in the public interest for the people, the transfer of land functions in Jatimulyo Village, including development with the aim of the concept of shared welfare, this very important thing was proven by at the time of the Prophet Muhammad, he built infrastructure in the form of; public wells, posts, roads, and markets.